Kampung pendidikan - Kampung’e Arek Suroboyo (KP-KAS), an innovative program to prevent obesity in Surabaya - Andani, Dian Puteri; Kuswandari, Luh Shanti (BKM Public Health and Community Medicine, 2021)
Objective: Food industry segmentation often targets teenagers, increasing during pandemics which contributes to diet and lifestyle changes that can lead to obesity. This habit began in elementary school due to the ignorance of children and parents towards nutrition and the availability of snacks and sugary food. Thus, control and a supportive environment are needed to prevent obesity among adolescents. Content: The Mayor of Surabaya held an annual competition to increase community empowerment through the Kampung'e Arek Suroboyo program, including Kampung Sehat and Kampung Pendidikan. This program could be an excellent opportunity to educate adolescents about the long-term effect of excessive sugar consumption by considering peer influence and socializing the obligation to put Nutritional Value Information in the small and micro-scale food industry. Furthermore, it involves the expertise to coach the citizen for two months. The women's association in the Family Welfare Movement (PKK) is an operational institution directly socialized with the community. Various health programs have proven successful with the PKK's synergy, from family planning (KB) to stunting. The empowerment movement has become a powerful weapon in dealing with health problems, including obesity. PKK advocacy through KP-KAS has great potential in shaping dietary behavior alteration in adolescents, as mothers play an essential role in food-related decision making. Therefore, there need to be additional KP-KAS assessment indicators, such as monitoring at the family level and grocery stores. Service delivery points of this program: 1) monitoring adolescent body weight from baseline to end line; 2) monitoring free-sugar added consumption in the school-based program; 3) monitoring Micro Small Medium Enterprises (UMKM) food products and products sold at the local stores already have food labels.